Molecular and Mesoscopic Dynamics Simulations on the Compatibility of PLA/Plasticizer Blends - 荆杰 乔青安 靳月庆 马翠花 蔡红兰 蒙延峰 蔡政亭 冯大成 (Chinese journal of chemistry, 2012)
The compatibility of the blend systems for olyactic acid （PLA）/tributyl citrate （TBC） and PLA/glycerol has been studied by molecule and mesoscopic dynamics methods. The results from glass transition temperature simulations showed that the compatibility of PLA/TBC system was better than that of PLA/glycerol, which were consistent with the conclusion obtained from the pair correlation functions. Besides, the behaviors of phase state distribution and evolution process were investigated by mesoscopic dynamics method as well. The results indicated that citrate ester was a better plasticizer than glycerol for PLA.